Effect of Soil Profile Moisture Levels, Seed Rates and How Spacings on Chickpea Yield - Saini, S S; Singh, J P; Faroda, A S (Annals of Arid Zone, 2016)
Effect of initial soil profile moisture (100, 150 and 200 mm/m), seed rates (25, 40 and 55 kg/ha) and row spacings (30, 60 and 90 cm) on the performance of chickpea was studied. The soil moisture levels of 150 and 200 mm/m gave similar grain yield of chickpea but they were significantlyÂ·better than 100mm/m soil moisture level. The row spacings of 30 cm and 60 cm gave significantly higher grain yield than 90 cm row spacing. The 30 and 60 cm row spacings were, however, comparable. There was significant increase in the yield of chickpea with 40 kg seed/ha over 25 kg seed/ha. Seed rate higher than 40 kg/ha did not increase the yield significantly.